Children's Drawing as a Projective Measure to Understand Their Experiences of Dental Treatment under General Anesthesia - Ziad D. Baghdadi; Saffana Jbara; Nazeem Muhajarine (MDPI AG, 2020)
Purpose: The overall aim of the study was to gain a deeper understanding of 3 to 10 year-old children's experiences, main concerns, and how they manage attending hospital for dental treatment under general anesthesia (DTGA). Methods: Twelve children aged 3-10 who were scheduled for DTGA were interviewed. In addition to tape-recorded interviews, data were collected using video diaries, participant observations, and pre-, peri-, and postoperative drawings. The children's drawings (n = 43) were analyzed using the Child Drawing: Hospital Manual (CD:H) and Vygotsky postulations for context readings, with the aim to explore what it means for children to undergo DTGA. Results: The analysis found that the main concern for children during the pre-operative period was that they were forced to prepare for an unknown experience, which elicited stress. This situation was handled during the peri-operative period by trying to recover control and to cooperate despite fear, stress, and anxiety. Drawings completed post-operatively showed the surgical mask, "stinky" smell of the anesthetic gas, and multiple extraction of teeth were the main troubling experiences for children. Several weeks after DTGA, children tried to regain normalcy in their lives again. Conclusion: This study contributed to a deeper understanding of how children as young as 3 years undergoing DTGA experience and express their lived experiences: emotional, psychological, physiological, or physical stress in the context of DTGA.